Public Relations Campaign PT. Kimia Farma Tbk Dalam Meningkatkan Citra Perusahaan - Alfareji Febrian Hanom; Nabila Putri Meitana; Noni Nur Oktaviani; Alycia Febytha Maruti; Tria Patrianti (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Kimia Farma, in enhancing its corporate image, has undertaken various communication campaigns as part of their efforts to build a positive image in the eyes of the public. PT. Kimia Farma is also actively involved in disseminating health-related information through their official social media channels, and they engage in various collaborations to boost public trust. The objective of this research is to understand and explore the campaigns carried out by PT. KAEF Kimia Farma Tbk in improving the company's image. The data collection techniques employed by the researcher include interviews, observations, and documentation. The research findings indicate that the image of PT. Kimia Farma Tbk has improved significantly following the campaigns they have conducted.